1999
DOI: 10.1007/s001700050100
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Drill Flute and Cutting Angles

Abstract: The analysis of drill cutting angles is important for the design of high-performance drill geometry. The cutting angles along the cutting edge of a drill are determined by the combination of its flute and flank surfaces. This paper examines the analysis of both flute and flank surface models and the evaluation of drill cutting angles. A new mathematical model for an arbitrary drill flute face is developed by sweeping the polynomial representation of the flute cross-sectional curve along the drill axis, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Hazırlanan matamatiksel modeller ile yapılan analizler, kesme açılarının delik hatalarına %5 oranından daha az etki ettiğini göstermiştir [10]. Hocheng…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Hazırlanan matamatiksel modeller ile yapılan analizler, kesme açılarının delik hatalarına %5 oranından daha az etki ettiğini göstermiştir [10]. Hocheng…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…Torque. Mechanical analysis of coal dust element drill pipe spiral groove is carried out, gravity and inertia force are neglected, and the external forces of coal dust are generalized as in Figure 2 [15,[18][19][20]. In Figure 2, denotes the unit width of the interface between coal dust element and the junk slot, denotes the thickness of coal dust in the direction of , ⃗ and ⃗ denote the normal force and friction, respectively, which are acted by drill pipe spiral groove, and ⃗ , ⃗ , and 0 denote the normal force, friction, and chip removal force, respectively, which are acted by hole wall on the outside surface of coal dust element.…”
Section: Calculation Of Chip Removalmentioning
confidence: 99%
“…The comparison between the analytical results and actual measured cutting angles of drill examples indicated that the average error is less than 5%. Ren and Ni [13] studied both the drill cutting angles and the flute surface models. They developed a new mathematical model to describe the drill flute and the drill flank face with a quadratic model illustrated according to the grinding parameters.…”
Section: Introductionmentioning
confidence: 99%